The dengue disquisition: A low-cost public housing conundrum in Klang Valley, Malaysia - Nabila AbuBakar; Jerzy M. Behnke; Norhidayu Sahimin; Xiaoye Kang; Siti Nursyahirah Mohd Shahar; Yvonne Ai Lian Lim; Siti Nursheena Mohd Zain (PLoS ONE, 2025)
Dengue remains the most rapidly advancing vector-borne disease in the world, and while the disease burden is predominantly in low-to-middle-income countries, the association with poverty remains in question. Consequently, a study was undertaken to evaluate the prevalence of anti-dengue antibodies among individuals residing in the People’s Housing Program (PPR), a government-sponsored low-cost housing initiative targeting low-income earners. This type of public housing often faces challenges, including substandard housing facilities. Therefore this study took into consideration several social determinants of health, including the economic, environmental, and social conditions that contribute towards dengue transmission. The research was conducted over a period of 18 months across 14 PPRs in Klang Valley, Malaysia. Overall seroprevalence of anti-dengue immunoglobulin G (IgG) was 78.2% (CL: 72.5–83.1) among the 436 residents who participated in the study, while seroprevalence of anti-dengue IgM was 0.9% (CL: 0.2–3.2). Log-linear statistical models with the presence/absence of anti-dengue IgG and individual factors showed significant associations of anti-dengue IgG with age, income, location, and waste bin conditions, but ethnicity was just at the wrong side of the cut-off for significance. However, a multifactorial model, in which all relevant factors were taken into account, showed that location and ethnicity were the key risk factors. For anti-dengue IgM, the only significant association was with the presence of stagnant water bodies around the compounds. Findings from this study highlight an acute need for improvements in the environmental and societal health of those residing in PPRs in locations that are particularly at risk, and continuous community empowerment to ensure that the preventive measures taken to eradicate dengue are locally sustainable.